Fate the hunter early Arabic hunting poems = Ṭardīyāt : min ʿaṣr mā qabla al-islām ḥattā 'l-ʿaṣr al-umawī - Montgomery, James E. 1962-; Montgomery, James E. 1962-; Sieburth, Richard 1949- (New York University Press, 2022)
"An anthology of Arabic hunting poetry from the pre-Islamic and early Islamic eras"--
Literaturverzeichnis Seite 187-191
Keywords: Araber; Lyrik; Arabisch; Jagd; Hunting / Poetry; Arabic poetry / To 622 / Translations into English; Poetry; Quelle; Fiktionale Darstellung